Pelatihan Pembuatan Kue Kering Modifikasi Sebagai Strategi Penguatan Cegah Stunting pada Paguyuban Wanita Patra: Modified Dry Cake Making Training as a Strategy to Strengthen Stunting Prevention in the Patra Women's Association - Hutajulu, Petrus Oktavianus; Nurmiati, Nurmiati (Politeknik Negeri Fakfak, 2024)
Stunting is a problem in children's growth and development due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below the growth standards for children in general. Fakfak Regency is one of the districts in West Papua province with a fairly high population with a population growth rate of 1.17% throughout 2021-2023. Lack of education regarding stunting for pregnant women and breastfeeding mothers is a problem that is often experienced in every region, this is also experienced in Fakfak district, especially in rural areas. The goal to be achieved in this service is that Patra women's associations in Fakfak district receive education about the nutrition needed by children to prevent stunting, reducing stunting rates in Fakfak district. The solution created to overcome community problems is by making modified cookies to prevent stunting from an early age, with these modifications it is hoped that children's nutritional needs can be met.